Foresight and trade-off analyses: Tools for science strategy development in agriculture and food systems research - Barrett, Christopher B.; Beaudreault, Amy R.; Meinke, Holger; Ash, Andrew; Ghezae, Nighisty; Kadiyala, Suneetha; Nigussie, Mandefro; Smith, Allison; Torrance, Lesley (Oxford University Press, 2021)
Foresight and trade-off analyses offer organizations such as CGIAR an opportunity to better prepare for alternative futures through adaptive research strategy and management. This essay introduces a set of papers that explore foresight and trade-off analyses within the context of the major reforms now occurring in the CGIAR. We tease out lessons not only for One CGIAR, but also for international development research organizations more broadly.